(untitled) (Eureka Journal of Civil, Architecture and Urban Studies, 2026)
This article discusses the development of gypsum carving in the Bukhara region since ancient times. Archaeological excavations (for example, the remains of the Varakhsha Palace) show that gypsum was widely used not only in building construction but also in wall decorations.